Sustainable Development Strategy of the Jakarta-Bandung High-Speed Train: Service Quality Reviewed from Passenger Satisfaction Levels - Prayudi; Mulyono, Agus Taufik; Najid; Sari, Endah Murtiana (International Journal of Innovative Research and Scientific Studies, 2025)
The rapidly developing business environment and the many choices that can be made by customers according to their desired expectations have caused companies to implement various innovations, especially in the selection of public transportation modes between Jakarta and Bandung, which are currently filled with travel cars, trains, high-speed trains, buses, etc. Companies innovate in order to create customer satisfaction, which in the long term will foster great loyalty. The purpose of this study was to determine the factors considered by passengers of the Jakarta-Bandung High-Speed Train to increase the level of satisfaction among service users. This study employs a quantitative method through a survey conducted on 300 respondents who used the Jakarta-Bandung High-Speed Train in January-February 2025, utilizing a questionnaire administered directly to respondents at Halim Station and Padalarang Bandung. To test the relationship between variables and validity, this study employs statistical analysis with structural equation modeling (SEM). The results of this study demonstrate a strong relationship between six dimensions: information services, accessibility, train service, train comfort, station comfort, and emergency actions, all of which contribute to increasing the satisfaction of Jakarta-Bandung High-Speed Train (HST) users. The findings of this study can be utilized by operators and the government in efforts to improve the level of Jakarta-Bandung train services and their regulations, as well as to plan the opening of new routes for HST in Indonesia in the future.